2020
DOI: 10.30699/ijp.2020.99403.1980
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Routine Repeat Testing of Critical Values in Various Working Shifts

Abstract: Scan to discover online Background & Objective: Accurate and timely reporting of critical values is an important issue. There is some doubt whether repeat testing of critical values would offer any advantage over single testing or not. The aim of this study was evaluation of utility of routine repeat testing of critical values in our referral center and to compare probable variations in different working shifts. Methods: Clinical results of serum Potassium, Calcium, Blood Hemoglobin and Prothrombin Time (INR: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…Nonetheless, this study did not explore if there is a specific list of tests to be repeated in case a critical value arises. Furthermore, Saffar et al [24] argue that repeating a test is unnecessary and might actually affect patient safety through delays in taking clinical action and the waste of resources [31], which is not similar to our results. A readback policy for critical value notification is often required of the responsible person delivering it [32], and nearly 79% of respondents assured they have such a policy to follow.…”
Section: Correct Answers Of Upper and Lower Limits And Units Of Criti...contrasting
confidence: 94%
See 1 more Smart Citation
“…Nonetheless, this study did not explore if there is a specific list of tests to be repeated in case a critical value arises. Furthermore, Saffar et al [24] argue that repeating a test is unnecessary and might actually affect patient safety through delays in taking clinical action and the waste of resources [31], which is not similar to our results. A readback policy for critical value notification is often required of the responsible person delivering it [32], and nearly 79% of respondents assured they have such a policy to follow.…”
Section: Correct Answers Of Upper and Lower Limits And Units Of Criti...contrasting
confidence: 94%
“…Approximately 45% of survey participants indicated that all critical values from a patient, including repeat measurements, are reported, which roughly matches the current study. The documenting of critical value reporting is required by the joint commission and other institutes [ 24 ]. All documentation is done for the purposes of quality monitoring, including notification time measurements, as reported by Piva et al [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some laboratory specialists report the result to the physician immediately, others verify it by re-running the test (5). However, given the technical advances and developments in laboratory measurements, the necessity of re-running panic values has been challenged in recent years (6). A Q-Probes study by the College of American Pathologists (CAP) revealed that 61% of laboratories routinely repeated tests for panic values, causing a 10 to 14-minute delay in reporting.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Saffar H et al, it was suggested that routine repeat of hematology and biochemistry critical test result was not necessary and it may adversely affect the patient safety measure. 15 CVN process implemented through a well-planned approach, rather than a commitment for clinical laboratories, is a right for the patient in order to ensure safety. It also plays a pivotal role in healthcare systems and has proved to be both cost saving and life saving.…”
Section: Introduction Of Critical Alert Sms Send Outs In Opd Casesmentioning
confidence: 99%